2022
DOI: 10.3390/antibiotics11121761
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Nanomaterials Based on Halloysite Clay Mineral: Research Advances and Outlook

Abstract: Bacterial infections represent one of the major causes of mortality worldwide. Therefore, over the years, several nanomaterials with antibacterial properties have been developed. In this context, clay minerals, because of their intrinsic properties, have been efficiently used as antimicrobial agents since ancient times. Halloysite nanotubes are one of the emerging nanomaterials that have found application as antimicrobial agents in several fields. In this review, we summarize some examples of the use of pristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that halloysite clay nanotubes effectively penetrate cell membranes due to their small cross-section [12]. In this case, halloysite penetrability is defined by their tens of nanometers diameter rather than their sub-micrometer length (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that halloysite clay nanotubes effectively penetrate cell membranes due to their small cross-section [12]. In this case, halloysite penetrability is defined by their tens of nanometers diameter rather than their sub-micrometer length (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the advantageous properties of the clays and clay minerals-ion exchange, adsorption, swelling, and rheological behavior-and their use as support [11][12][13][14][15], the pharmaceutical and cosmetic industries have an increasing interest in incorporating these materials to their products. In this sense, a special emphasis has been made in natural resources by their abundance, low cost, and environmental friendliness [16][17][18][19]. Thus, it is worth underlining the employment of clays in skin care formulations [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Clay minerals, because of their high biocompatibility, high availability, and low cost, represent emerging materials for application in biomedical field. [12,13] In the last years, there has been an increasing interest in the utilization of clay minerals not only as excipients in pharmacological formulations but also as active ingredients for the delivery of different drugs. [14][15][16] In this context, halloysite, a clay mineral with a typical hollow tubular structure, holds several advantages for biomedical applications.…”
mentioning
confidence: 99%